2006
DOI: 10.1176/ps.2006.57.6.871
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Help Seeking: How Sexual and Gender Minority Groups Access Mental Health Care in a Rural State

Abstract: Although persons from sexual and gender minority groups often experience positive outcomes as a result of help seeking, some LGBT people remain vulnerable to anti-LGBT sentiments that persist within secular and sacred sectors of rural health care systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 8 publications
6
67
0
Order By: Relevance
“…Willging et al studied rural lesbian, gay, bisexual and transgender populations seeking mental health care. 22 He conducted a series of interviews with patients to determine whether barriers to care based on the stigma associated with mental health exist in an already stigmatized population. This notion was confirmed, with one interviewee saying, 'We have our ways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Willging et al studied rural lesbian, gay, bisexual and transgender populations seeking mental health care. 22 He conducted a series of interviews with patients to determine whether barriers to care based on the stigma associated with mental health exist in an already stigmatized population. This notion was confirmed, with one interviewee saying, 'We have our ways.…”
Section: Resultsmentioning
confidence: 99%
“…We fix ourselves here.' 22 Some patients feel that they are the victims of the prejudice of their health care providers. 27 In South Carolina, Vyavaharkar et al studied the quality of life of HIV patients in the rural Southeast.…”
Section: Resultsmentioning
confidence: 99%
“…Disclosure to health care providers is critical to receiving appropriate care and it has been suggested that routine questions about Downloaded by [University of California, San Francisco] at 10:58 20 February 2015 sexual identity could assist in this process. However, studies have demonstrated that non-disclosure to health providers is not uncommon (Clover, 2006;Steele, Tinmouth, & Lu, 2006;Wilging, Salvador, & Kano, 2006). In addition, disclosure appears to be more difficult for lesbians, as well as gay and bisexual men of color (Bernstein et al, 2008;Klitzman & Greenberg, 2002).…”
Section: Program Implicationsmentioning
confidence: 99%
“…The negative relationship of self-reliant attitudes and help-seeking behavior has been portrayed as a byproduct of cultural values or preferences. For example, rural communities have been described as having cultures of self-reliance, and these attitudes are associated with underutilizing mental health services (Fuller et al 2000;Willging et al 2006). Ortega and Alegria (2002) found that for a community sample of Puerto Ricans living in low income areas on the island of Puerto Rico, self reliance was negatively associated with use of mental health services.…”
Section: Mental Healthcare Service Utilization and Ethnicitymentioning
confidence: 99%